2019
DOI: 10.1155/2019/4341056
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adsorption and Activation Behaviours of Carbon Dioxide over Copper Cluster (Cu4) and Alumina-Supported Copper Catalyst (Cu4/Al2O3) by means of Density Functional Theory

Abstract: The adsorption and activation of carbon dioxide over copper cluster (Cu4) and copper doped on the alumina support (Cu4/Al2O3) catalytic systems have been investigated by using density functional theory and climbing image nudged elastic band. The adsorption energies, geometrical configurations, and electronic properties are analysed. The results show the strong chemical interaction between the copper cluster and the alumina support. Both the Cu4 cluster and Cu4/Al2O3 systems have a high adsorption ability for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The generalized gradient approximation with Perdew–Burke–Ernzerhof (PBE) functional accounting for electron exchange-correlation energy is used to perform geometry optimizations and frequency calculations and determine thermochemical properties of the species. The PBE functional is found to be suitable for studies using copper clusters and surface catalysts as numerous research studies have demonstrated the advantage of utilizing the PBE functional in investigating Cu systems, yielding highly accurate results that align closely with the experimental values. ,,,, Along with it, a density fitting triple-ζ valence with double polarization (def2TZVPP) basis set is incorporated as it proves to minimize the basis set superposition error (BSSE), giving errors of <0.04 eV . In addition to this, the Grimme-D3 dispersion correction was incorporated into our study to account for the effect of the van der Waals interaction on the structure and electronic properties of the species .…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The generalized gradient approximation with Perdew–Burke–Ernzerhof (PBE) functional accounting for electron exchange-correlation energy is used to perform geometry optimizations and frequency calculations and determine thermochemical properties of the species. The PBE functional is found to be suitable for studies using copper clusters and surface catalysts as numerous research studies have demonstrated the advantage of utilizing the PBE functional in investigating Cu systems, yielding highly accurate results that align closely with the experimental values. ,,,, Along with it, a density fitting triple-ζ valence with double polarization (def2TZVPP) basis set is incorporated as it proves to minimize the basis set superposition error (BSSE), giving errors of <0.04 eV . In addition to this, the Grimme-D3 dispersion correction was incorporated into our study to account for the effect of the van der Waals interaction on the structure and electronic properties of the species .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, the utmost necessity to mitigate CO 2 has gained the interest of researchers all around the globe to come up with promising strategies for its capture and valorization. Over the last two decades, enormous research efforts have been accomplished to develop novel and cleaner technologies for sucking out excess CO 2 from the atmosphere and converting it to different value-added products such as methane, methanol, carbon monoxide, ethanol, and other hydrocarbons . Among the various chemicals, formic acid (HCOOH) proves to be a potential chemical for its capability to be utilized for the transportation and storage of H 2 , the future fuel of civilization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation